Analisis Efektivitas Program Pertukaran Mahasiswa Merdeka Dalam Mendorong Pertukaran Akademik dan Budaya - Fajri Fajri; Dewi Widya Ningsih; Reza Mauldy Raharja; Wika Hardika Legiani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The Merdeka Students Exchange (PMM) is one of the programmes of Mardeka Learning Campus Merdeca (MBKM) that has been created by the Ministry of Education, Culture, Research and Technology. (Kemendikbudristek). During one semester, student exchange programmes enable Indonesian students to study at leading universities in their homeland, bringing diverse cultural experiences and strengthening academic cooperation as well as student learning experiences. The programme has become one of the important initiatives in enhancing academic and cultural cooperation among students. The research is aimed at the effectiveness of PMM programmes in achieving the objectives of academic and cultural exchange. The research methods used in the analysis are qualitative through in-depth interviews with students participating in the PMM program. Research findings show that PMM has successfully facilitated the exchange of academic knowledge and broadened cultural understanding among students. Challenges such as language constraints and cultural adaptation were also identified as factors affecting the effectiveness of the program. The implications of these findings are discussed to provide recommendations for better recommendations in the planning and implementation of future PMM programmes.